Combinations of potent topical steroids, mercury and hydroquinone are common in internationally manufactured skin‐lightening products: a spectroscopic study. (26th July 2015) - Maneli, M. H.; Wiesner, L.; Tinguely, C.; Davids, L. M.; Spengane, Z.; Smith, P.; van Wyk, J. C.; Jardine, A.; Khumalo, N. P.
Summary: Background: The topical steroids betamethasone (BM) and clobetasol propionate (CP) are illegal in cosmetics. Hydroquinone (HQ) and mercury (Hg) are either illegal or allowed only in limited concentrations (2% and 1 ppm, respectively). Aim: To investigate active ingredients and countries of origin of popular skin‐lightening products available in Cape Town, South Africa. Methods: In total, 29 products were examined; of these, 22 products were purchased from informal vendors, and 2 products (out of a total of 29) were purchased over the counter. HQ, Hg 2+ and steroids were quantified by high‐performance liquid chromatography–ultraviolet spectrophotometry, inductively coupled plasma‐mass spectrometry and liquid chromatography–mass spectrometry, respectively. Results: Of the 29 products, 22 (75.9%), all imported and bought from informal vendors, contained illegal or banned ingredients: 13 (44.8%) contained steroids (9 CP, 4 BM), 12 (41.4%) contained Hg (30–2300 ppm), and 11 (37.9%) contained HQ. Sequentially, the products originated from Italy (27.3%, n  = 6), India (22.7%, n  = 5), the Democratic Republic of Congo (DRC) (22.7%, n  = 5), Cote d'Ivoire (9.1%, n  = 2), USA (9.1%, n  = 2), UK (4.5%, n  = 1) and France (4.5%, n  = 1). Two products, one from India and one from the DRC, contained all four ingredients (HQ, Hg, BM, CP). Of the 12 products containing Hg, 10 also contained HQ and/or a steroid, yet none listed Hg as an ingredient. A significant proportion of the steroid‐containing products (76.9%) also contained at least one other skin‐lightening agent. Not all internationally available products were tested, which is a limitation of the study. Conclusion: In spite of a European Union ban on skin lighteners, a third of the products tested were from Europe. Combinations of Hg and ultrapotent steroids were prominent. International law enforcement and random testing is needed to encourage industry compliance and help protect consumers.